Influence of growing-phase supplementation strategies on intake and performance of different beef cattle genotypes in finishing phase on pasture or feedlot - Simioni, Tiago A. [UNESP]; Torrecilhas, Juliana A. [UNESP]; Messana, Juliana D. [UNESP]; Granja-Salcedo, Yury T. [UNESP]; Vito, Elias San; Lima, Ana R.C. [UNESP]; Sanchez, João M.D. [UNESP]; Reis, Ricardo A. [UNESP]; Berchielli, Telma T. [UNESP] (Elsevier, 2021)
The objective of this study was to evaluate the effect of previous supplementation strategies (mineral and corn-based supplementation in the growing-phase) on intake and performance of different beef cattle group genotypes in the finishing phase on pasture or feedlot. Two experiments for the finishing phase were conducted simultaneously. For Exp.1, 60 bulls were finished on tropical grass with supplementation. They were distributed in a randomized block design in a 3 × 2 factorial arrangement (three genotypes (Nellore, Senepol x Nellore (½Senepol), Angus x Nellore (½Angus)) and two growing-phase supplementation strategies (mineral and corn-based supplementation)). They were allocated to 12 paddocks with 1.8 ha of Urochloa brizantha ‘Xaraes’ per paddock (5 animals/paddock). The animals were supplemented (corn-based supplement at the rate of 20 g/kg body weight [BW]) for 125 days. For Exp.2 60 bulls were finished in individual pens. They were of three genotypes (Nellore, ½Senepol, ½Angus) from two growing-phase supplementation strategies (mineral and corn-based supplementation) and distributed in a randomized block design allocated to individual pens. In Exp.1 (finish on tropical grass), the genotypes,½ Angus and Nellore bulls showed the greatest initial (end of growing phase treatments) and final body weights (BW), final carcass weight (HCW) and hot carcass yield (HCY) than ½ Senepol bulls. Bulls with corn-based supplementation in the growing phase had greater initial (end of growing phase) and final BW and lower feed efficiency (FE) than animal supplementation with mineral in the growing phase. ½Senepol showed higher total dry matter (DM, percentage of BW) and forage DM intake than Nellore in the finishing phase. For supplement DM intake, higher values were found for the ½ Angus bulls compare ½Senepol. Nellore bulls showed greater DM and OM digestibility than ½ Senepol but no different to ½ Angus. For experiment 2 (finish in feedlot), ½ Angus and ½ Senepol bulls had higher ADG than Nellore bulls. ½ Angus and Nellore bulls presented the greatest HCW while Nellore bulls had the highest HCY. Daily carcass gain (DCG) in the finishing phase was higher in animals that received only mineral supplementation during the growth phase. ½ Angus and ½ Senepol showed higher FE than Nellore bulls. Nellore bulls had lower DMI of forage and supplement than ½ Angus and ½ Senepol. ½ Angus and Nellore bulls had greater BW at the end of the finishing phase than ½ Senepol.The feedlot-finishing system promotes better finishing performance in ½ Angus and ½ Senepol, thus crossing Nellore with a Bos taurus breed may be a strategy to improve finishing performance and carcass characteristics. Corn-based supplement during the growing phase may be a strategy to improve body weight on entry to a finishing phase, although it may reduce carcass gain in the finishing phase.
Keywords: Bos indicus; Bos taurus; Carcass; Crossbreeding; Digestibility